Consumption, Extraction, Recharge and Availability of Water in the Main Subsectors of the Mexican Manufacturing Industry, Regional Levels - Ledesma, Dora (Archives of Business Research, 2022)
If the consumptive use of water in agriculture, domestic, thermoelectric plants and service enterprices does not decrease, will the water be available for consumption in the manufacturing industries? There is no certainty of the availability of this resource in the medium or long term. Aquifer recharge depends on temperature-precipitation cycles and desalination processes, where appropriate. Using gray forecast models, linear and non-linear regression, the main sustainability indicators were calculated considering the subsectors that most demand water, to obtain a medium-term vision, applying scenarios to 2030 of status of resource at the national level, (administrative) water region and federative entity, as well as, by surface or underground source. Pollutant aspects or water quality were not considered. The results show the urgent decision-making to ensure the availability of water.